Effect of diet and method of feeding on performance of pigs weaned at three weeks of age - Clarkson, J.R.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four trials involving 600 pigs weaned at 15 to 23 days were conducted to evaluate pig performance as affected by added whey and method of feeding during the first week after weaning. Pigs fed 20% dried whole whey gained faster the first two weeks after weaning and during the 35-day trial than did pigs fed a milo-soybean meal diet with no whey. Ten percent dried whole whey did not improve performance over that of the control diet, and 30% dried whey showed no advantage over the 20% whey diet. Pigs fed delactosed whey substituted on a protein basis for 20% dried whole whey performed the same as those fed 20% whole whey. Adding lactose to the basal diet did not improve pig performance. Pigs fed the 20% whey diet for the first two weeks and the control diet for the last three weeks of the trial performed similar to those fed the 20% whey diet during the entire 35-day trial. By feeding a whey diet for only two weeks, total cost of gain is greatly decreased.
Keywords: Swine; Feeding; Performance; Weaning